Generating better leaf traits in M2 lines of fourteen Ethiopian sesame (Sesamum indicum L.) genotypes through the treatment of their seeds with sodium azide. Issue 12 (December 2022) - Weldemichael, Micheale Yifter; Baryatsion, Yemane Tsehaye; Sbhatu, Desta Berhe; Abraha, Girmay Gebresamuel; Juhar, Hagos Mohammedseid; Kassa, Abraha Birhan; Sibhatu, Fiseha Baraki; Gebremedhn, Hailay Mehari; Gebrelibanos, Tesfakiros Semere; Mossa, Mohammed Mebrahtu; Berhe, Birhanu Debesay; Gebru, Haftay Abadi
Abstract: The present study explored the effect of sodium azide (NaN3 ) on quantitative and qualitative leaf traits of M2 lines on 14 Ethiopian sesame genotypes collected from Humera Agricultural Research Center, Tigrai, Ethiopia. Qualitative data on leaf color, leaf hairiness, leaf arrangement, leaf shape, basal leaf profile, basal leaf margin, and leaf angle to main stem as well as quantitative data on length of basal leaf, length of top leaf, width of basal leaf, width of top leaf, length of marginal leaf, and width of marginal leaf were recorded and analyzed using analysis of variance, clustering analysis, Mahalanobis distance, and principal component analysis. Generally, treatment of seeds with NaN3 has brought many distinct and statistically significant phenotypic changes on both quantitative and qualitative leaf traits of the M2 lines. The changes in the NaN3 treated and locally adapted genotypes of Gumero and Zeri Tesfay are promising; producing the highest mean length of basal leaf ( p ≤ 0.01). NaN3 treated seeds of Baha Necho, Gumero, and Hirhir developed the highest mean width of basal leaf. Locally adapted genotypes have responded positively to NaN3 treatment, generating better leaf traits as compared to the research improved ones. This study was the first of its kind in exploring the effects of NaN3 seed treatment on leaf traits of sesame genotypes. The findings of this study will, therefore, serve as a steppingstone to look into the effects of the changes in sesame yield and initiate future genetic and molecular studies on the responsive genotypes. Abstract : Clustering; Qualitative leaf traits; Quantitative leaf traits; Sesame indicum ; Sodium azide.